2008
DOI: 10.1080/16066350801983723
|View full text |Cite
|
Sign up to set email alerts
|

HIV Sexual Risk Behaviors among Ketamine and Non-Ketamine Using Criminal Offenders Prior to Prison Entry

Abstract: This study is the first to examine ketamine use and its association with HIV sexual risk behaviors among a criminal offending population in the United States. Data were collected from 716 inmates as part of the Transitional Case Management (TCM) protocol within the Criminal Justice Drug Abuse Treatment Studies (CJ-DATS) cooperative agreement. Bivariate analyses were used to identify differences between ketamine users (n=44) and non-ketamine users (n=672). Three Poisson regression models were used to identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Bottoms are often in a submissive position during anal sex and younger than those who have the top role, which may in turn result in a lower awareness or reduced ability in terms of selfprotection (62). On the other hand, the MSM who engaged exclusively or predominantly in receptive anal intercourse would be more likely to use recreational drugs and have unprotected receptive anal intercourse (URAI) (63), as the effects of recreational drugs in relaxing the anal sphincter and in reducing pain during anal intercourse (64)(65)(66), which carries a higher risk for HIV infection in the absence of condom use. For those who engaged in both receptive and insertive anal intercourse, studies show versatile sexual roles could have more occasional sex partners or engage in UAI frequently (60,62,67).…”
Section: Risk Factors Associated With Hiv Infectionmentioning
confidence: 99%
“…Bottoms are often in a submissive position during anal sex and younger than those who have the top role, which may in turn result in a lower awareness or reduced ability in terms of selfprotection (62). On the other hand, the MSM who engaged exclusively or predominantly in receptive anal intercourse would be more likely to use recreational drugs and have unprotected receptive anal intercourse (URAI) (63), as the effects of recreational drugs in relaxing the anal sphincter and in reducing pain during anal intercourse (64)(65)(66), which carries a higher risk for HIV infection in the absence of condom use. For those who engaged in both receptive and insertive anal intercourse, studies show versatile sexual roles could have more occasional sex partners or engage in UAI frequently (60,62,67).…”
Section: Risk Factors Associated With Hiv Infectionmentioning
confidence: 99%
“…A study conducted in Mainland China showed that significantly less connectivity of the thalamic nuclear groups with the prefrontal cortex, the motor cortex/supplementary motor area, and the posterior parietal cortex in ketamine users compared to non-ketamine users 24 . Because ketamine is a club drug that can harm executive functions, its users are likely to engage in high-risk behavior that can lead to HIV infection 25 , 26 and reckless driving 11 . Two studies found that frequent ketamine use and any ketamine use were associated with sexually risky behavior 25 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Because ketamine is a club drug that can harm executive functions, its users are likely to engage in high-risk behavior that can lead to HIV infection 25 , 26 and reckless driving 11 . Two studies found that frequent ketamine use and any ketamine use were associated with sexually risky behavior 25 , 27 . Young adults under the influence of various club drugs were shown to be at greater risk than non-users of engaging in dangerous behavior such as unprotected sex, thus facilitating the transmission of infectious diseases 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Females in a relationship with violent partners have four times the risk of contracting a sexually transmitted disease, including HIV (CDC, 2018). Oser et al . (2008) suggested that criminal offenders are at higher risk for both contracting and transmitting HIV, particularly due to increased substance abuse and sexual risk-taking behaviors; however, the prevalence of HIV risk-taking behaviors among substance abusing male offenders of IPV and the effects on their females partners is still undetermined.…”
mentioning
confidence: 99%